Prevalence of impaired glucose tolerance and insulin resistance among obese children and adolescents - Robabeh Ghergherechi; Ali Tabrizi (Dove Medical Press, 2010)
Robabeh Ghergherechi1, Ali Tabrizi21Department of Pediatrics Endocrinology, Tabriz University of Medical Sciences, Tabriz, Iran; 2Students’ Research Committee, Tabriz University of Medical Sciences, Tabriz, IranPurpose: Obesity is one of the most important nutritional disorders in the world which has an obvious relationship with the incidence of metabolic diseases. Obesity prevalence has increased among children and adolescents during recent decades, leading to a rise in Type 2 diabetes mellitus (DM II) prevalence in these two age brackets. Hence, the aim of this study was to assess impaired glucose tolerance and insulin resistance, and gather metabolic findings in obese children and adolescents.Methods and materials: We studied 110 obese children and adolescents (body mass index > 95th percentile for age and gender) 4–18 years of age referred to the endocrine clinic of the Children’s Hospital at Tabriz University in a descriptive cross-sectional study. Fasting glucose, insulin, and lipid profile in all subjects were determined. Oral glucose tolerance test after eating 75 g/kg glucose was performed. Homeostatic model assessment was used to estimate insulin resistance.Results: Impaired glucose tolerance and insulin resistance prevalence in 68 obese adolescents was 14.7% and 31.8%, respectively. Impaired glucose tolerance and insulin resistance was not seen in 23.8% of 42 obese children. No case of DM II was seen. There was a significant statistical difference in glucose (P = 0.003) and insulin (P < 0.001) level at minute 120 in individuals with impaired glucose tolerance compared to obese children and adolescents without impaired glucose tolerance. Rate of insulin resistance in patients with impaired glucose tolerance was greater and had a significant statistical difference (P = 0.03).Conclusion: Obesity has a close relationship with increased risk of impaired glucose tolerance and insulin resistance in children and adolescents. Oral glucose tolerance test, unlike fasting glucose test, is a benefit test to predict impaired glucose tolerance. With prompt identification and treatment of obese children with impaired glucose tolerance, we can prevent it from progression towards DM II.Keywords: impaired glucose tolerance, insulin resistance, obesity